The Beijing Platform for Action charted a future we still need to bring up: building feminist economic policy - Esquivel, Valeria Renata (2020)
The Beijing Platform for Action (BPfA), written 25 years ago, is remarkable in its economic diagnostics, analytical framework, and policy prescriptions, which remain fully relevant today. In this article, we revisit the main economic problems identified by the BPfA: GDP growth, employment, care, and poverty. In terms of GDP growth, the BPfA was clear that not any type of growth would suffice, calling for sustainable development avant la lettre. It left open the question of what feminist macroeconomics would look like, on which there has been much progress in defining, if unfortunately not in applying. On employment, it is still the case that sectoral, labour, and employment policies, working in tandem with macroeconomic policies, are necessary to make the promise of decent work for all a reality. On care, this 25 years saw the transition from ‘valuation to transformation’, complementing and deepening the BPfA’s agenda; and the need for social protection for all remains key to alleviate poverty. In the most challenging of times, while the COVID-19 crisis is unfolding, the BPfA charts a future that we urgently need to bring up.